Promoting the "Cempaka Tegal Slumpring Market" Tourism Through E-Tourism : Benchmarking Approach - Mubarok, Abdulloh; Gashimov, Elchin; Rahmatika, Dien Noviany; Gashimov, Denis; Susilawati, Agnes Dwita; Amalia, Mei Rani; Firmansyah, Fahmi; Hapsari, Yustia; Prasetyono, Agus (Jurnal Pengabdian UNDIKMA, 2024)
This community service aims to socialize the concept of digital promotion to introduce the Cempaka Tegal tourist village to the community in a wider area, both locally, nationally and internationally. The method of implementing this service uses socialization and benchmarking. Data collection was carried out through observation and interviews which were then analyzed descriptively. The results of this activity showed that the practice of implementing digital promotion of tourist attractions in the Samara province of Moscow, Russia can be applied to introduce Cempaka Tegal Slumpring Market Tourism to all corners of the world. The digital promotional practices include creating official websites for tourist attractions, utilizing social media such as Facebook, Instagram, and Twitter, utilizing virtual and augmented reality (VR/AR) technology, collaborating with influencers and travel bloggers, optimizing search engines (SEO) and provide a tourist village tourism application. Some of these promotional media have now been implemented, such as Facebook (Desa Wisata Cempaka, n.d.),Â  Instagram (instagram.com/explore/locations/351643408686716/), collaboration with travel bloggers (Agus Fadilah, n.d.).